Constructing dual ionically cross-linked poly(acrylamide-co-acrylic acid) /chitosan hydrogel materials embedded with chitosan decorated halloysite nanotubes for exceptional mechanical performance. (1st August 2020) - Li, Shi-Neng; Li, Baoqiang; Yu, Zhi-Ran; Li, Yang; Guo, Kun-Yu; Gong, Li-Xiu; Feng, Yujie; Jia, Dechang; Zhou, Yu; Tang, Long-Cheng
Abstract: Hydrogels with exceptional mechanical properties at high water content are crucial need for practical applications in various fields. However, achieving a hydrogel possessed splendid mechanical performance with well trade-off between tensile strength and toughness is highly demanded due to the mechanical weakness of conventional hydrogel. Herein, we report a novel kind of nanocomposite hydrogel developed by integrating chitosan decorated halloysite nanotubes (CS-f-HNTs) into dual cross-linked structure composed of chemical and Fe 3+ induced ionically cross-linked network. Combining the nanoparticle reinforcement with physical interactions including hydrogen bonds among polymer chains and ionic coordination interaction between Fe 3+ ions and functional groups on chitosan chains and the copolymer chains, the hydrogel exhibits extraordinary and balanced mechanical performance, including high strength (3.06 MPa), outstanding stretchability (>2000%) and superior toughness (47.6 MJ m −3 ) in which water content remains ~80 wt%. Based on microstructure observation and dynamic mechanical behavior analysis, we demonstrated that the addition of CS-f-HNTs effectively bridged polymer chains via physical interactions and strengthened dual cross-linked network, leading to significant improved mechanical properties. Moreover, the hydrogels also possessed remarkable self-recoverability (97.9% for small strain (200%) and 91.5% for large strain (1000%)) at room temperature and the related mechanism was discussed. The strategy developed herein may provide a newfound avenue in the design and development of strong and tough hydrogel for promising applications in loading-bearing structural materials. Graphical abstract: Image 1 Highlights: Chitosan decorated halloysite nanotubes are served as effective reinforcement in hydrogel system. The nanocomposite hydrogel displays prominent and balanced mechanical properties. Excellent self-recovery property can be achieved for the nanocomposite hydrogel. Nanoparticle reinforcement and physical interactions contribute to enhanced mechanical properties.